2017
DOI: 10.1007/s10815-017-1065-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pregnancy outcome by extending embryo culture in IVF-ET during clinical application

Abstract: The extended culture of day 3 embryos for 7-8 h not only reduced the risk of IVF-ET treatment compared to blastocyst culture through another 2-3 days, but also improved the clinical outcomes and the efficiency of every transferred cycle and every transferred embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…[ 4 ] Thus, day 3 post-fertilization is a critical period for human embryos to initiate EGA. Consistent with previous studies, [ 3 , 4 ] most available embryos (80.47%) in our study developed to the 4 to 8-cell stage on the morning of day 3. The EC of 7 to 8 h provided a short time for viable embryos to trigger EGA, and some embryos with SDP (57.63%) continued developing.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…[ 4 ] Thus, day 3 post-fertilization is a critical period for human embryos to initiate EGA. Consistent with previous studies, [ 3 , 4 ] most available embryos (80.47%) in our study developed to the 4 to 8-cell stage on the morning of day 3. The EC of 7 to 8 h provided a short time for viable embryos to trigger EGA, and some embryos with SDP (57.63%) continued developing.…”
supporting
confidence: 93%
“…Thus, implantation rates remain at 20% to 30% in IVF-ET. [ 3 ] During IVF-ET treatment, we found that more than half of day 3 embryos continued developing during an extended culture (EC) of 7 to 8 h from 08:00–09:00 to 16:00, and live birth rates increased when these embryos were transferred. Then, this strategy was used to improve live birth rates during IVF-ET.…”
mentioning
confidence: 99%
“…In a clinical context, normal embryos should develop at the 8-cell stage 3 days after IVF 31 ; however, there were embryos that were fertilized, as evidenced by the formation of pronuclei, that remained arrested at the 1-cell stage 32 . Zygotic arrest of some embryos was due to gene mutations, such as TUBB8 mutations that affect cell division 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used light (LM) and transmission electron microscopy (TEM) to describe the morphological changes occurring in pre-implantation mouse embryos (at the 2-cell, 4-cell, morula and blastocyst stage), following in vitro culture under physiologic (5%) and atmospheric (20%) concentrations of O 2, using in vivo embryos flushed out of the uterus as controls. Furthermore, we focused our analysis on the blastocyst stage, since embryo transfer at this stage is common, with increased occurrence of healthy singleton live birth [20,21]. These data will help us to understand how variations of O 2 concentrations can affect, to what extent and at which stage, the ultrastructure of murine embryos cultured in vitro.…”
Section: Introductionmentioning
confidence: 99%